(untitled) (Research, Society and Development, 2021)
Costume jewelry may expose skin to toxic metals due to sweat and friction, causing intoxications. An investigation was conducted over costume jewelry rings to study its behavior and verify its safety throughout their use, regarding toxic metal contamination. Qualitative and quantitative elemental analysis of the internal and external layers of the ring samples (costume jewelry) were made through X-Ray Fluorescence Spectrometry (XRF) and Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). The ring samples were also immerged in a synthetic sweat solution for 30 days. The lixiviated solution and post treated surfaces were analyzed by ICP-OES and Search Electron Microscopy (SEM), respectively. Metals such as Cu, Cd, Cr and Ni were identified in the surface composition, as well in the composition of the digested samples. The synthetic sweat eroded the rings surfaces, and metals such as Cd and Mn were lixiviated by it. The results indicate the presence and lixiviation of harmful metals that may cause health and environmental problems.